In Memory of Tibor Frank (1948-2022) - Bollobás, Enikő (FOCUS: Papers in English Literary and Cultural Studies, 2022)
First, a brief account of his family background: Tibor Frank came from a Jewish Hungarian family with a rich history. His ancestors included Mór Wahrmann, Hungary’s first Jewish member of Parliament after the 1867 Compromise, and the initiator of the unification of Pest, Buda and Óbuda in the Pest Parliament. At the beginning of the 2000s, on the initiative of Tibor Frank, a small street in Új- Lipótváros was named after Wahrmann (when it became clear that the street which had once borne his name, but had since become Victor Hugo Street, could not be returned to its original name). At the same time, the Hungarian Academy of Sciences established the Mór Wahrmann Award, and in 2009, a collection of Mór Wahrmann’s papers, collected meticulously by Tibor Frank, was published under the title Honszeretet és felekezeti hűség [Patriotism and Religious Loyalty], referring to the nineteenth-century politician’s fundamental position and the dual commitments that were central to his political activities. As Wahrmann wrote, “One cannot be a true patriot without being true to one’s creed, or a good citizen while neglecting religion. One’s ardent patriotism must go hand in hand with unbreakable loyalty and devotion to one’s faith.”